At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
1st is true
i dont think the first is true amistre it should be 9/x^3
rsvitale i think youre right about number one
you might be right :) without () around it count it as seperate right..
66. false 67. true by distributive property. (-1/6)*(x^2+3x) 68. false you're only multiplying the top by 5 it should be 5x^2/6 69. false you need to divide the first term by 3y as well 70. false 71.false same reasoning as 70. I can explain these if you want. 72.true x^2-8x+16=(x-4)^2. then take the square root. 73.true ln(e^2)=2ln(e) 74.false e^(l+s)=(e^l)*(e^s)
wow lol ok lets start with 67...why did you multiply by -1/6?
70 and 71: assume sqrt(x+y)=sqrt(x)+sqrt(y) square both sides x+y=x+2sqrt(x)*sqrt(y)+y this is not true unless x,y, or both are 0 so the equality cannot be true
dividing by -6 is the same as multiplying by (-1/6)
dividing by anything is the same as multiplying by its inverse.
inverse as in 1/something, not the technical definition of inverse
do the other ones make sense?
ok and well im still going down the list trying to see if i get it. are you sure 73 is true? b/isnt 2lne not the same thing as just 2 by itself?
2lne=2. the equality is ln(e^2)=2 ln(e^2)=2ln(e)=2. ln(e)=1
e to what power=e? e^1=e
oh ok for some reason i thought lne^2=1
no ln(e^2) means e to what power is e^2. so it is 2.
ok so if i said e^27 it would be 27 correct?
ok and i dont get the last one
(e^l)^(s)=e^(l*s) not e^(l+s)
do you want me to explain why?
but i thought when you multiply exponents you add them like (x^5)(x^3)=x^8
yeah that is right. But you are multiplying e^l by itself s times. (e^l)^s=(e^l)*(e^l)*(e^l)*....*(e^l) <---- s times =e^(l+l+l+l....+l <---s times)= e^(l*s)
oohhh ok i get it!! well thanks so much for your help!!
you're welcome :)